UJI DAYA TERIMA DAN NILAI GIZI BAKSO YANG BERBAHAN DASAR TEPUNG RUMPUT LAUT - Rahmi .; Etti Sudaryati; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Meatballs  is a preferably  snack  food allcircles.  Meatballs  had interesting  a spherical shape and  savory flavor. This research  aims to determine the acceptability test and  iodine content and crude fiber of modified meatballs with Seaweed flour and tapioca flour. This  experimen  designt  was  completely  randomized  design  with  of  two  factors  are Seaweed flour and tapioca flour with composition of 30%:10%, 20%:20%, 10%:30%.  Test acceptability  meatballs modified Seaweed flour and tapioca flour  30  students people of the Faculty  of  public  health  University  North  Sumatera  and  nutrient  analysis  was  tested  in laboratory  of  industrial  research  and  standarization  Agency  Medan   and  Biochemistry Faculty Mathematics and Natural Sciences.The  results  organoleptic  test  based  on  color,  aroma,  flavor,  and  texture  meatballs showed  the  most  preferred  are  meatballs  mixture  of  seaweed  flour  20%  and  tapioca  flour 20%. The result of nutrional content analysis showed that three treatments has content ofiodine 74,03 mg/kg, 49,79 mg/kg, 26,11 mg/kg and crude fiber 9,7%, 7,4%, 3,4%.Then  suggested  so  that  citizen  can  be  meatballs  modified  with  seaweed  flour  and tapioca flour as a food alternatives because it contains iodine and crude fiber required the body.Keywords:  Meatballs,  Seaweed  flour,  Tapioca  flour,  Acceptability  test,  Nutrient composition